Mexican origin Youth and the Gang Context: Social Identities and School Experiences - Leticia Villarreal Sosa (International Journal of School Social Work, 2016)
Youth, gang involved or not, living in a community with a gang problem are impacted in various ways. This study draws from qualitative interviews over the transition to high school of thirty-two Mexican origin students in Chicago. The Extended Case Method (ECM) was employed for the analysis of the qualitative data. Using borderlands and social identity theory, results indicated that the school response to the youth gang problem directly impacted students’ educational experiences, how staff viewed them, and how they negotiated these social categorizations. Students reported unrecognized trauma due to the level of violence and marginalizing experiences in school. An understanding of the importance of school supports is a critical first step in addressing these issues.
Keywords: social identity; gangs; trauma; Mexican youth; school dropout